Persepsi khalayak terhadap isu-isu pendidikan sastera perpaduan - Chew, Fong Peng (Universiti Kebangsaan Malaysia, 2008)
May 13 1969, racial riots in Malaysia carried the message that ethnic relations in this country is fragile. In order to foster the sense of unity, many national policies have since been implemented. Hence, the teaching of national integration in Malay literature has more or less become an educational goal to achieve the objectives of the policy. Thus, an empirical study based on the theory of Social Background, involving 1,600 students from Form IV, Form VI, university and graduate teachers in Malay studies is the focus of this paper. The findings of the study indicate that 66.48% of the respondents are in favor of teaching the literature of integration in all educational institutions. Upon further analysis, Malay women of high socio-economic status tend to be more inclined to the idea compared with non-Malay male from low socio-economic status. The results from the study suggests an improvement in the integration through education is effective